(untitled) (Altre Modernità, 2016)
The movie Seediq Bale, directed by Wei Te-Sheng and produced by John Woo, is a Taiwanese historical drama epic film based on the Wushe Incident in 1930. The story depicts the Wushe Incident, which happened in central Taiwan while it was under Japanese rule. Mona Rudao, a then chief of Seediq indigenous village Mahebu, led warriors against Japanese authorities due to the long-term colonial oppression. In response, the Japanese mounted a relentless counter-attack, killing over three hundred Seediq people. Often compared by the media in Taiwan to the films Braveheart and The Last of the Mohicans, the film, released in 2011, is so far the most expensive production in Taiwan cinema history. Different language registers are present in the movie, including Mandarin, Japanese, and the Seediq language; this can be a great challenge for the translator when translating the subtitles into English. Nonetheless, it is believed that ideologies can be manifested in language use. So, the study attempts to disclose the translator¡¦s hidden indigenous ideologies in the English subtitles s/he provided. Moreover, as subtitling translation involves a multiplicity of verbal and non-verbal semiotic modes, those visual and audio elements could also contribute to the final product of subtitle translations. Hence, the study, in addition to the translator¡¦s indigenous ideologies and handling of ethnic issues in translation, also looks at how the translator worked with semiotic modes in designing the subtitles for the target context.